Innovative logistics for the transportation of sand and gravel in Brazil. Issue 4 (4th October 2010) - Aguirre, A.B.; Hennies, W.T.; Marks, A.
The transportation of sand and gravel, which are highly consumed in civil construction, is traditionally hauled on roads and highways. Currently, the growing demand in large metropolitan areas is met by an increasing road fleet, which delivers the aggregates from the origin to construction sites. This paper discusses alternative distribution means for aggregates in Sao Paulo, Brazil, focusing on the cost-reduction opportunities associated with the use of railway and waterway modals. The benefits identified in the research are not merely limited to greater competitiveness due to the reduction of costs in logistics, but also to reducing traffic jams.